Simulation models on the ecology and management of arable weeds : structure, quantitative insights, and applications - Bagavathiannan, Muthukumar V. (2020)
Fil: Bagavathiannan, Muthukumar V. Texas A and M University. Department of Soil and Crop Sciences. College Station. USA.